Factors of food premises not attaining "A" grading in Sabah, Malaysia Borneo - Narinderjeet Kaur; Wafaak Esa; Yanti Zahlan; Jiloris F Dony; Syed Sharizman Syed Abdul Rahim; Mohammad Saffree Jeffree; Khamisah Awang Lukman; Mohd Faizal Madrim; Zulkhairul Naim Sidek Ahmad (Horizon Research Publishing, 2021)
Introduction: Up to 70% of the food-water related illness is related to food services hygiene and safety standard. An important and crucial enforcement operation conducted by this division is the inspection of premises and food sampling. This is of paramount importance as food premise grading is directly related to consumers’ health and safety which is in line with the third United Nations Sustainable Developmental Goal of good health and wellbeing. Aim: This study aims to identify the components and factors that are commonly related with food premises that do not obtain an “A” grading. Methodology: A cross-sectional study was conducted in 2017 among 315 food premises in Kota Kinabalu, Sabah that were under the jurisdiction of The Kota Kinabalu City Hall. Data from the food premise inspection forms were reviewed and analysed via multivariate analysis. Results: Premises that were non-compliant with health checks on all food handlers (OR 36.72, 95% CI 10.00-135.44), poor condition of the toilets (OR 6.96, 95% CL 2.35-20.63), ineffective fly control (OR 10.35, 95% CI 1.91-56.02), no availability of garbage cans (OR 3.01, 95% CI 1.01-9.01) and no separate storage for food items and chemical (OR 3.11, 95% 1.06-9.07) were significantly associated with not obtaining “A” grading. Conclusion: More focus and attention need to be paid to these factors not only for premises to attain “A” grading but also to improve the safety and hygiene of food that is consumed by the public.